Level Of Competence in The Development of Children's Visual Abilities and Creativity in Preschool Education - D.Burkhonova (Genius Journals, 2021)
The world's leading international organizations and developed countries have jointly adopted the concept of education until 2030, paying special attention to the education system. The concept states that "the educational process is an activity that determines the main driving force, source and strategy of development of any country." In order to organize quality education at the level of world standards, on the basis of modern requirements, students need to be formed as physically healthy, spiritually and intellectually developed, independent individuals, to reveal their creative abilities, to be ready for reading, systematic education and nurturing a passion for the process
Keywords: Level of competence; development; children's visual ability; creativity